If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(9 + -1x) = 176 (9 * 11 + -1x * 11) = 176 (99 + -11x) = 176 Solving 99 + -11x = 176 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-99' to each side of the equation. 99 + -99 + -11x = 176 + -99 Combine like terms: 99 + -99 = 0 0 + -11x = 176 + -99 -11x = 176 + -99 Combine like terms: 176 + -99 = 77 -11x = 77 Divide each side by '-11'. x = -7 Simplifying x = -7
| 2(7x-7)=-126 | | X^2+11=-5 | | X+2x=318 | | 185(.166)= | | -6p=3p+54 | | 5m-3+2m=m+2+m | | 7(p+9)-3=2p-7 | | x^2-5x+20=-5 | | 4x+6x=-1 | | 3-8[2-(7y-3)]= | | 0.7(x-2)= | | 2x+6-4x=y | | 5x-6=60 | | 10-2x=30-10x | | 8(2-3)=24 | | 2(3x-8)=3(5x-2) | | -14x-2=12 | | 3x^3-33x^2+72x=0 | | 60/a= | | f(x)=7x^2+28x | | Cos(x)+1=-cos(x) | | (-288/(x^2))=0 | | (-288/(x^^2))=0 | | (9x^2-7x-1)/(12x^2-1) | | 4x+2+7x-19=34 | | 96=15-x | | 6v^2-13v-5=0 | | 51+3x=-5x+75 | | k^2+14k+50=0 | | log(3x+1)=logx | | 10x-2y=82 | | sin^2-1=0 |